2016
DOI: 10.12688/f1000research.9157.1
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of an ecological wastewater treatment plant’s microbial communities and their potential to metabolize pharmaceuticals

Abstract: Pharmaceuticals and other micropollutants have been detected in drinking water, groundwater, surface water, and soil around the world. Even in locations where wastewater treatment is required, they can be found in drinking water wells, municipal water supplies, and agricultural soils. It is clear conventional wastewater treatment technologies are not meeting the challenge of the mounting pressures on global freshwater supplies. Cost-effective ecological wastewater treatment technologies have been developed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 85 publications
1
27
0
Order By: Relevance
“…During one research, metagenomic sequencing of plasmid DNA from municipal wastewater-treatment plants displayed, that genes involved in heavy metal resistance are disproportionately abundant in plasmid DNA in comparison to the entire genome. The same study showed, that genes involved in the transformation and degradation of organic pollutants are also mostly present in plasmids [24]. Such knowledge has already been applied, and plasmids with genes responsible for toluene degradation were successfully transferred to aerial plant endophytes and increased the total degradation of contaminant that would have been volatilized [26].…”
Section: Metagenomic Approach To Enhance Phytoremediation Efficiencymentioning
confidence: 88%
See 2 more Smart Citations
“…During one research, metagenomic sequencing of plasmid DNA from municipal wastewater-treatment plants displayed, that genes involved in heavy metal resistance are disproportionately abundant in plasmid DNA in comparison to the entire genome. The same study showed, that genes involved in the transformation and degradation of organic pollutants are also mostly present in plasmids [24]. Such knowledge has already been applied, and plasmids with genes responsible for toluene degradation were successfully transferred to aerial plant endophytes and increased the total degradation of contaminant that would have been volatilized [26].…”
Section: Metagenomic Approach To Enhance Phytoremediation Efficiencymentioning
confidence: 88%
“…Introduction of plants to highly degraded and contaminated soils may augment both the quantity and quality of microbial populations occurring in bulk soil [24]. Although plant-microbe interactions are incredibly complex and sensitive to different environmental conditions, plants can favour certain species that promote its growth or inhibit the activity of pathogens.…”
Section: Metagenomic Approach To Enhance Phytoremediation Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these problems, some authors prefer to skip the assembly step and proceed to the direct functional/taxonomic annotation of the raw reads, especially when the aim is to obtain a functional or taxonomic profile of the metagenome [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Workers have also studied antibiotic-resistant genes in WWTP reactors (Christgen et al, 2015), and their mobility among organisms within plants (Munck et al, 2015;Wang, et al, 2013). Other works are illuminating capacities to decompose pharmaceuticals (Balcom et al, 2016) and phenol (Silva et al, 2012) in wastewaters. And another has identified possible biological mechanisms contributing to concrete corrosion (Gomez-Alvarez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%